Neutrophilic eccrine hidradenitis: A new culprit-carbamazepine - Bhanu, Prakash (Medknow Publications & Media Pvt Ltd, 2013)
Neutrophilic eccrine hidradenitis (NEH) is a distinctive dermatosis occurring in patients with malignancy or undergoing chemotherapy. This disorder is characterized by a neutrophilic infiltrate around the eccrine glands and secretory coils, and is associated with necrosis. It must be distinguished from infections, drug eruptions, malignancies or other forms of skin diseases. As it is a self-limiting condition, establishing the diagnosis will avoid unnecessary investigations and treatment. Here we report a case of NEH in a 40-year-old woman suspected to be due to carbamazepine.